The Application of Cooperative Learning Model Type Index Card Match to Improve Student Learning Outcomes on The Subject Matter of The Proclamation of Independence Class V SD Negeri 025 Huraba - Khodijah Nasution; Rahmi Seri Hanida; Ali Yusron (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to improve the learning outcomes of fifth-grade students of SD Negeri 025 Huraba on the Proclamation of Independence material through the application of the Index Card Match cooperative learning model. The study used the Classroom Action Research (CAR) method which was implemented in two cycles, with each cycle including the planning stage, action implementation, observation, and reflection. The research subjects were 22 fifth-grade students of the 2023/2024 academic year. Data were collected through teacher and student activity observation sheets and learning outcome tests. Data were analyzed using qualitative and quantitative analysis techniques. The results showed that the application of the Index Card Match model was able to improve learning activities and student learning outcomes. The average teacher activity increased from 80.00 in cycle I to 95.71 in cycle II. Student activity also increased from 63.38 to 91.55. Meanwhile, the average student learning outcomes increased from 68.64 in the initial condition to 77.36 in cycle I and 84.55 in cycle II. These findings indicate that the Index Card Match type of cooperative learning model is effective in increasing student activity and learning outcomes on the Proclamation of Independence material in class V of SD Negeri 025 Huraba.